2023
DOI: 10.1002/anie.202218625
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Capsule Catalysis Enables the Exploration of Terpenoid Chemical Space Untapped by Nature

Abstract: Terpenes represent the largest and the most diverse class of natural compounds. This is remarkable as the whole variety is accessed from just a handful of highly conserved linear precursors. Modification of the cyclization precursors would enable a dramatic expansion of the accessible chemical space. However, natural enzymes do not enable us to tap into this potential, as they do not tolerate larger deviations from the prototypical substrate structure. Herein we report that supramolecular capsule catalysis ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Supramolecular capsule and cage catalysis have been recently increasingly utilized to perform selective reactions that are difficult to perform with small-molecule catalysts. We reported that the supramolecular hexameric resorcin[4]­arene capsule I (Figure A) is able to catalyze the conversion of α-glycosyl halides into β-glycosides in high selectivity. , Several points are noteworthy about this methodology. (1) The capsular catalyst enabled the formation of β-pyranosides as well as β-furanosides from the respective α-configured donors under nearly identical reaction conditions (Figure C).…”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular capsule and cage catalysis have been recently increasingly utilized to perform selective reactions that are difficult to perform with small-molecule catalysts. We reported that the supramolecular hexameric resorcin[4]­arene capsule I (Figure A) is able to catalyze the conversion of α-glycosyl halides into β-glycosides in high selectivity. , Several points are noteworthy about this methodology. (1) The capsular catalyst enabled the formation of β-pyranosides as well as β-furanosides from the respective α-configured donors under nearly identical reaction conditions (Figure C).…”
Section: Introductionmentioning
confidence: 99%